Antibodies and anti-antibodies specific to estradiol and progesterone and tumor proliferation in breast cancer patients - A. N. Glushkov; E. G. Polenok; L. A. Gordeeva; P. V. Bayramov; N. E. Verzhbitskaya; A. V. Antonov; G. I. Kolpinsky; M. V. Kostyanko (Сибирский онкологический журнал)
The study was aimed to determine the interrelations between levels of serum antibodies specific to estradiol and progesterone (IgA1-E2 and IgA1-Pg) and corresponding antiidiotypic antibodies (IgG2-E2 and IgG2-Pg) and tumor Ki67 positive cells in breast cancer patients (BCP). Material and Methods. The content of these antibodies in the blood serum of BCP (522 at the I stage and 578 at the II –IV stages) was studied using non-competitive enzyme immunoassay. Ki67 was determined using immunohistochemical method. Statistical analysis of the results was performed using the Statistica 8.0 software. Results. There were no revealed the desired associations in BCP I stage. Tumors with high levels of Ki67 positive cells (>20,0 %) were found more often in BCP II –IV stages with high serum levels of IgA1-E2 together with IgA1-Pg than in BCP with low levels of these antibodies (68.8 vs 58.0 %, р=0.02). In contrast, tumors with Ki67>20,0 % were revealed less often in BCP with high levels of IgG2-E2 together with IgG2-Pg (49.6 vs 65.2 %, р=0.002). Tumors with high levels of Ki67 positive cells were revealed in 42.9 % BCP I stage and in 77.1 % BCP II –IV stages with high serum levels of IgA1-E2 and IgA1-Pg in combination with low serum levels of IgG2-E2 and IgG2-Pg (p<0.001). There were no such differences between BCP I and II -IV stages with low levels of IgA1-E2 and IgA1-Pg in combination with high levels of IgG2-E2 and IgG2-Pg (46.7 vs 48.2 %, accordingly, р=0.985). Conclusion. Antibodies against E2 and Pg synergistically promoted, but corresponding antiidiotypic antibodies synergistically inhibited the tumors proliferation in BCP. Immunoassay of antibodies and anti-antibodies to steroids is recommended for research of human hormone-dependent neoplasms progression.